Vytautas’s Name in the Names of the Northern Black Sea Region - Белецкая, Ольга (Lietuvos istorijos studijos, 2018)
[full article and abstract in Russian; abstract in English] This research deals with the study of the toponyms of the Northern Black Sea Region, in which the name of Vytautas, Grand Duke of Lithuania, is fixed. The data of written (documentary, narrative, cartographic) and archaeological sources are considered concerning nine objects: The Bathhouse of Vytautas (1, 2, 3), the Wade of Vytautas, the Bridge of Vytautas, the Hillfort of Vytautas, Vytautas’s Tower, Vitovka and Lake Vidovo. The author has come to the conclusion that all the names are mentioned in the later sources. The results of the article may be interesting to all who study the activity of Vytautas as well as to scholars dealing with the historical geography of the Northern Black Sea Region.